To Formulate and Evaluate the Herbal Gel Using Woodapple Pulp Extract - Vinit Isankar; Kavita Pandey; Vanshita Bobde; Jagdish Baheti (Asian Journal of Pharmaceutical Research and Development, 2025)
The creation of herbal formulations, especially in cosmetics and pharmaceuticals, has been spurred by the growing desire for natural medicinal treatments. The goal of this study is to develop a new herbal gel with pulp from wood apple (Limonia acidissima) as the main component. Well-known for its therapeutic qualities, woodapple is a good choice for skincare because it is high in antioxidants, phenolics, vitamins, and minerals. The goal of the study was to create a stable, potent gel and evaluate its phytochemical and physicochemical properties as well as its benefits for the skin.Carbopol 940 and additional ingredients were added to a gel foundation to guarantee stability and skin compatibility after the pulp from fresh wood apple fruits was extracted. The gel’s pH, viscosity, homogeneity, stability, spreadability, and microbiological safety were assessed. Bioactive substances, including flavonoids, tannins, and saponins that contribute to anti-inflammatory and antioxidant properties, were validated by phytochemical analysis.During stability testing, the gel showed no phase separation or microbiological contamination, good viscosity, and appropriate pH (5.5–6.5). All formulations exhibited antibacterial action against S. aureus and E. coli, but the F1 formulation was noticeably more effective, particularly against S. aureus. The medicinal potential of woodapple in herbal skincare treatments is highlighted in this study.